SPECIFIC CHARACTERISTICS OF IMPLEMENTING THE COMBINED METHOD OF TEACHING FOREIGN LANGUAGES IN WESTERN UKRAINE AND IN RUSSIA (1918-1939) - Богдана Лабінська (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The paper investigates the specific characteristics of implementing the combined method in teaching foreign languages in Western Ukraine and in Russia (1918-1939). Preconditions of the origin of the combined method have been ascertained. Teaching language aspects and communicative activities has been analyzed on the basis of curricula, manuals and scientific articles of those times. Comparative studies of foreign language teaching methodology in Ukraine and in Russia have been carried out. Fundamentals of the combined method of teaching foreign languages have been substantiated and peculiarities of their realization in the region under investigation have been formulated.